The Influence of Celebrity Endorsers on Purchasing Intention through the Shopee Application with Brand Trust as Mediation Variable - Citra Fitrah Nuraida; Sri Nastiti Andharini; Novita Ratna Satiti (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the effect of celebrity endorsers on purchasing intention through the Shopee application with brand trust as a mediating variable. The variables in this study include celebrity endorsers, purchasing intention, and brand trust as mediating variables. The population in this study is people who have seen Shopee advertisements and become potential consumers of Shopee. The sample in this study amounted to 140 respondents determined by the purposive sampling method. The data analysis technique used is path analysis. Data was collected by distributing questionnaires. The results of the study show that celebrity endorser has a positive and significant effect on brand trust and purchasing intention. Brand trust has a positive and significant effect on purchasing intention. Brand trust can mediate the influence of celebrity endorsers on purchasing intention. It can be interpreted that if the brand trust variable increases, the influence of the celebrity endorser variable on purchasing intention also increases. The results of the study are intended for Shopee marketing actors to be more selective in choosing celebrity endorsers and this research can be used in future research.